Convergence in the functional properties of forelimb muscles in carnivorans: adaptations to an arboreal lifestyle?. (25th August 2018) - Taverne, Maxime; Fabre, Anne-Claire; Herbin, Marc; Herrel, Anthony; Peigné, Stéphane; Lacroux, Camille; Lowie, Aurélien; Pagès, Fanny; Theil, Jean-Christophe; Böhmer, Christine
Abstract: The arboreal environment is complex and irregular and imposes significant constraints on the locomotor ability of vertebrates, resulting in morphological adaptations. Carnivorans are of particular interest because they radiated several times independently into the arboreal milieu, leading to convergence in long bone anatomy. We investigated whether the forelimb muscles show differences in arboreal vs. terrestrial species and tested for convergence in muscle architecture. To do so, we studied the forelimb muscles in 17 species of carnivorans with different locomotor modes (arboreal and terrestrial). Our results showed that the forelimb musculature evolved in a convergent manner in arboreal species, resulting in more forceful and heavier wrist rotators and elbow flexors, even when accounting for phylogeny. This suggests that selective forces imposed by the environment drive the evolution of the muscular system towards a convergent phenotype that provides a functional advantage for locomotion in the complex three-dimensional arboreal habitat.